Effect of advanced platelet-rich fibrin and concentrated growth factor on tissues around implants in maxillary anterior region - Akanksha Gopal Shetye; Manu Rathee; Prachi Jain; Vipul Agarkar; Smriti Kaushik; Maqbul Alam (Wolters Kluwer Medknow Publications, 2022)
Aim: To assess the effect of advanced platelet-rich fibrin (APRF) and concentrated growth factor (CGF) on tissues around implants in the maxillary anterior region. Settings and Design: This was a prospective clinical study. Materials and Methods: Thirty subjects were divided into three groups with 10 dental implants in each group, i.e., Group 1: Control group, Group 2: Endosseous implant placement with APRF, and Group 3: Endosseous implant placement with CGF. The subjects were assessed at baseline (at the time of prosthesis placement), 2 weeks, 2 months, 6 months, and 1 year for modified sulcular bleeding index, periimplant probing depth, mucosal suppuration, bleeding on probing, crestal bone level as well as implant stability. Statistical Analysis Used: Oneway Analysis of variance and Post hoc Bonferroni were the statistical tests used. Results: The difference in implant stability at 2 months was significantly (P < 0.05) more among the control and CGF groups compared to APRF group. However; the crestal bone levels, periimplant probing depth, modified sulcular bleeding index, mucosal suppuration, and bleeding on probing were statistically non-significant (P > 0.05). Conclusion: CGF and APRF accelerated osseointegration. Furthermore, they had a positive effect on stabilization values. However, CGF showed better results and with further clinical trials may show a positive effect on implant healing period.